Oxygen extraction from air employing adsorption technology - Seah, Jaymus Min Yew (Nanyang Technological University, 2022)
This research is aimed at improving oxygen purity extracted from air using a Pressure Swing Adsorption Device in the Energy Systems Laboratory by examining various parameters such as mass flow rate, pressure of feed gas, purge flow rate, adsorption, and pressurization Time. In the experimental setup, molecular sieves from silica gel, zeolite JLOX-101, and 13X are used to adsorb water vapor, nitrogen, and carbon dioxide, respectively.